2005
DOI: 10.1161/circulationaha.105.556886
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fish Oil on Heart Rate in Humans

Abstract: Background-The effect of fish oil on heart rate (HR), a major risk factor for sudden death, is not well established. We calculated this effect in a meta-analysis of randomized, double-blind, placebo-controlled trials in humans. Methods and Results-Randomized trials of fish oil that evaluated HR were identified through MEDLINE (1966

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
116
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 351 publications
(131 citation statements)
references
References 58 publications
13
116
0
2
Order By: Relevance
“…Raised HR per se is a risk factor for CVD (16) . A recent study utilising the HR-lowering drug ivabradine has found that reducing HR below 70 bpm reduced the incidence of CHD (25) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Raised HR per se is a risk factor for CVD (16) . A recent study utilising the HR-lowering drug ivabradine has found that reducing HR below 70 bpm reduced the incidence of CHD (25) .…”
Section: Discussionmentioning
confidence: 99%
“…There is strong evidence that regular consumption of LC n-3 PUFA can also reduce HR. In a meta-analysis of thirty-two trials, Mozaffarian et al (16) found that fish oil consumption for greater than 12 weeks reduced HR, particularly with groups that had a resting HR equal to or above 69 bpm. However, in the present study, we did not find a significant reduction in resting HR, perhaps because resting HR in the present study was below 69 bpm for each group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review measured changes in heart rate after n-3 PUFA combining all patients groups, and including two trials with patients with type 2 diabetes, showing pooled reductions of about 2 beats/min [53]. In the population-based study, 4 beats/min was shown to be the difference between patients who died a sudden death and the controls.…”
Section: Discussionmentioning
confidence: 99%
“…The biological effects of n-3 FA on atherosclerosis include preventing arrhythmias [8,12,[19][20][21][22][23][24], decreasing platelet aggregation [27][28][29], lowering plasma triglycerides [30][31][32][33][34][35], increasing HDL cholesterol and LDL particle size [36][37][38][39][40], decreasing blood pressure [42][43][44][45], reversing cholesterol accumulation from atheromatous plaques [46,47] and decreasing inflammation [48][49][50].…”
Section: Biological Effects Of N-3 Fa Related To Cvdmentioning
confidence: 99%